Numerical Analysis of Erosion Caused by Biomimetic Axial Fan Blade - Jun-Qiu Zhang; Zhi-Wu Han; Hui-Na Cao; Wei Yin; Shi-Chao Niu; Hui-Yuan Wang (Advances in Materials Science and Engineering)
Damage caused by erosion has been reported in several industries for a wide range of situations. In the present work, a new method is presented to improve the erosion resistance of machine components by biomimetic method. A numerical investigation of solid particle erosion in the standard and biomimetic configuration blade of axial fan is presented. The analysis consists in the application of the discrete phase model, for modeling the solid particles flow, and the Eulerian conservation equations to the continuous phase. The numerical study employs computational fluid dynamics (CFD) software, based on a finite volume method. User-defined function was used to define wear equation. Gas/solid flow axial fan was simulated to calculate the erosion rate of the particles on the fan blades and comparatively analyzed the erosive wear of the smooth surface, the groove-shaped, and convex hull-shaped biomimetic surface axial flow fan blade. The results show that the groove-shaped biomimetic blade antierosion ability is better than that of the other two fan blades. Thoroughly analyze of antierosion mechanism of the biomimetic blade from many factors including the flow velocity contours and flow path lines, impact velocity, impact angle, particle trajectories, and the number of collisions.